Telaah Akademik terhadap Teori Behavioristik: Klasifikasi teori, Pemikiran tokoh, dan Penerapannya dalam Pendekatan Pembelajaran - Salsabila Nurhasanah; Fariha Romadloniyah; M. Yunus Abu Bakar (Indo Publishing, 2026)
Learning is a crucial process aimed at modifying students’ behavior for the better. One theory that explains this is behavioristic learning theory, which emphasizes the relationship between stimulus and response that can be observed and measured. This theory focuses more on observable behavior rather than cognitive processes. Figures such as Ivan Pavlov, John B. Watson, B.F. Skinner, Edward Thorndike, and Edwin Guthrie made significant contributions through the concepts of classical conditioning, operant conditioning, connectionism, and contiguity. In its implementation, this theory highlights the importance of the environment, reinforcement (reward), and punishment in shaping students’ learning habits and behavior. Teachers function to manage stimuli in order to produce responses that align with instructional objectives, making the learning process more planned, systematic, and focused on measurable outcomes. Therefore, behavioristic theory plays a significant role in improving learning outcomes and shaping students’ behavior effectively and purposefully.